ANALISA PROSES PEMBELAJARAN ONLINE DI MASA PANDEMI COVID 19 MAHASISWA ADMINISTRASI PERKANTORAN POLITEKNIK LP3I JAKARTA - Faridah Faridah (JURNAL LENTERA BISNIS, 2021)
The outbreak of the COVID-19 has made everyone experience changes in their daily lives. Learning activities must still run even though they are online. The purpose of this research is to describe the online learning process during the pandemic for LP3I Jakarta Institute of Technology Faculty of Business Administration Student, Depok campus. This type of research is a qualitative description. Data - data collected using observation techniques, interviews and literature. The data analysis technique uses the Miles & Huberman model by utilizing the google meet application. From the results of the data analysis it can be concluded that the online learning process at the LP3I Politkenik Jakarta, Depok campus is going quite well. Even though at the beginning of the pandemic, students felt dissatisfied with learning to use online. But basically they prefer learning to be done in person (off line) than online. The positive side of online learning is that students are better able to solve the problems they experience and are more courageous in speaking and more technologically literate. However, in practice, there are still a small number of students who have problems, such as frequent network breaks, expensive quota purchases, and lecturers not knowing the seriousness of student learning because they do not meet face-to-face. Suggestions submitted should lecturers increase creativity for the purpose of achieve maximum learning goals and students can be more motivated to take part in learning, research on learning to keep going to be developed and improved for the advancement of education, provide training to educators on the latest technology and the Government provides quotas more evenly to students.Keywords: Process, Online Learning, Covid-19 Pandemic,Office Administration